Porto, cidade e ambiente natural: questões, políticas e instrumentos de interfaces urbanística e ambiental na Grande Vitória (ES) - Silvestre, Henrique Alexandre (2019)
Changes in port structures, operations and activities invariably interfere with the relationship between the city and its ports. In the context of today's globalized competition, technological demands become imperative, intensify the role of territories as attractive to global capital and modify the port and city interface. This generates a strengthening of the trend of ports around the cities. In Vitória, capital of Espírito Santo, the trajectory of its ports is aligned with the trajectory of its urban occupation, being these elements of beaconing in the socioeconomic, political, cultural and urban local environmental life. Vitoria passed from the city-wharf to large port complexes, from the founding port to the internalized dry ports, constituting in the 21st century an infrastructural system articulated in transport networks and logistics of extensive global reach. The port sites are implemented - mostly - by means of cancellation processes of the surrounding cities. Public policies related to the port and urban dynamics in Brazil allow to elucidate part of the problematic about the port city and the impacts in the territory. Although Vitória and region present an intrinsic economic and social connection with its port system, this list can not be seen as a safeguard to obliterate the surrounding environment. In this dissertation, we will discuss port activity and its environmental interface through expansions, notably landfills and territorial expansions. Likewise, the port theme will be consulted in the planning instruments of the three federative spheres. As a result, there is a lack of debates at the municipal, regional, state and federal levels on ports and impacts on the surrounding natural and urban environment. It is concluded that the port issue is mainly marked by interests globalized in dissonance with the public, social, environmental and local development interests.